The marathon (precompetitive preparation) - Velikorodnih, Y.; Kozmin, R.; Konovalov, V.; Nechaev, V. (Soviet Sport Review, 1986)
The precompetitive activities of 30 Russian marathoners were analyzed after an important marathon in Vilnuse when it was thought that many of them would perform in the 2.10 - 2.11 region. However, despite previous very fast sub-60 min 20 Km races five weeks before the marathon, none of them came close to the predicted and expected levels of performance. Thus, a retrospective analysis of training was performed. For a marathon, the authors suggest that the range of training intensities should be restricted over the last four weeks with the volume of work decreasing weekly. This way the athlete will be primed for a particular range of performance capabilities but will also be rested. Implication: Exaggerated speed training in a taper for a marathon has no value for enhancing performance or preparing properly. The speeds of training should be restricted to the range that is likely to be experienced in the event but as the taper progresses even that range should be reduced further to about 50% of the original range. Rather than being exactly (one speed) specific, the concept of performance range tapering should be employed. Any taper speeds outside of those expected to be performed in a contest are likely to be destructive and predispose the athlete to poorer performances.